2015
DOI: 10.1002/aelm.201500062
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Induced Control of Photoconductive Gain and Doping in a Hybrid Graphene–Quantum Dot Transistor

Abstract: concentration can be modifi ed, and photoresponsivity of SLG can be signifi cantly enhanced by the choice of ligands. By reducing the length of capping ligands, hence the thickness of the dielectric barrier between the QDs and the SLG, and by preserving the integrity of the ligand layer, we achieve the efficient transfer of photogenerated carriers from the QDs to the graphene before recombining, resulting in enhanced photoresponsivities of up to ≈10 9 A W −1 .Single layer graphene grown by low-pressure chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 31 publications
7
67
0
Order By: Relevance
“…Ligand exchange processes are commonly used to replace the long-chain ligand with small molecules such as amines [32], thiols [33][34][35], and hydrazine [36]. However, it can be difficult to stabilize QDs such as PbS and PbSe using short surfactant ligands, as both size and shape of the dots can be compromised during the exchange process [35][36][37][38][39][40][41].…”
Section: Fabrication Technologiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Ligand exchange processes are commonly used to replace the long-chain ligand with small molecules such as amines [32], thiols [33][34][35], and hydrazine [36]. However, it can be difficult to stabilize QDs such as PbS and PbSe using short surfactant ligands, as both size and shape of the dots can be compromised during the exchange process [35][36][37][38][39][40][41].…”
Section: Fabrication Technologiesmentioning
confidence: 99%
“…However, it can be difficult to stabilize QDs such as PbS and PbSe using short surfactant ligands, as both size and shape of the dots can be compromised during the exchange process [35][36][37][38][39][40][41]. In their work on QD solids, Jeong et al demonstrated complete removal of oleic acid on PbS QDs using ethanedithiol (EDT) and mercaptocarboxylic acids (MPA) treatments to fabricate QD solids with enhanced mobility and lifetime [33].…”
Section: Fabrication Technologiesmentioning
confidence: 99%
See 3 more Smart Citations